2012
DOI: 10.3109/0886022x.2011.647302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Non-diabetic Renal Disease and Role of Renal Biopsy in Diabetic Patients with Renal Involvement: A Single Centre Review

Abstract: Background: Type 2 diabetes mellitus (T2DM) is reportedly the leading cause of end-stage renal disease (ESRD) worldwide. However, non-diabetic renal diseases (NDRD) are not uncommon among T2DM patients with renal involvement. Our study aimed to examine the prevalence of NDRD in T2DM and clinical markers for diabetic nephropathy (DN) and NDRD and to determine the role of renal biopsy in T2DM patients and its impact on clinical practice. Methods: We conducted a retrospective analysis of T2DM patients in whom ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
74
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 27 publications
25
74
4
1
Order By: Relevance
“…The relatively low screening rates in Korea compared to the Western countries are likely to be due to the difference in the health system, economic situations and national demographics [22]. Chong et al [23] reported the role of renal biopsy in diabetic patients with renal involvement. In the DN subgroup, Indian patients had a significantly shorter duration of diabetes on renal biopsy compared with Malays and Chinese patients.…”
Section: New Biomarkersmentioning
confidence: 99%
“…The relatively low screening rates in Korea compared to the Western countries are likely to be due to the difference in the health system, economic situations and national demographics [22]. Chong et al [23] reported the role of renal biopsy in diabetic patients with renal involvement. In the DN subgroup, Indian patients had a significantly shorter duration of diabetes on renal biopsy compared with Malays and Chinese patients.…”
Section: New Biomarkersmentioning
confidence: 99%
“…Information on serum creatinine values was available in 34 studies [6, 7, 9-11, 13, 15-17, 19-21, 23-25, 27-29, 31, 33, 34, 37, 38, 42-48, 50-53]; in 10 of these studies the majority of patients had mean serum creatinine levels falling roughly within the normal range (<1.43 mg/dL) [16, 20, 25, 28, 31, 42-44, 51, 52]. In 12 studies mean values ranged from 1.44 to 3.00 mg/dL [7,10,13,23,25,27,29,34,37,45,47,53] while the remaining 12 included patients with quite severely compromised renal function (serum creatinine >3 mg/dL) [6,9,11,12,15,19,21,24,33,38,46,50]. Data on estimated glomerular filtration rate (eGFR) were available in 16 of the above-mentioned studies reporting information on serum creatinine [7, 10, 13, 15-17, 19-21, 28, 34, 42, 48, 51-53].…”
Section: Study and Participants' Characteristicsmentioning
confidence: 99%
“…FSGS prevailed in six cohorts [12,16,21,32,33,50], (17 [12] to 37.7% [16]). Acute interstitial nephritis was the main NDRD in four studies [9,11,17,24] (18 [24] to 48.8% [11]). The analysis of the different histological pictures of NDRD according to the population background showed a significantly higher percentage of IgA diagnosis in studies on Asian populations compared with European (mean percentage of IgA diagnosis: 21.3 versus 8.2%, P ¼ 0.003) and American studies (21.3 versus 9.4, P ¼ 0.04).…”
Section: Prevalence Of Dn Ndrd and Mixed Forms And Pooled Analysesmentioning
confidence: 99%
“…NDRD is rare in type 1 diabetes mellitus, particularly in patients with a history of diabetes of >10 years [5]; however, reports of the prevalence of NDRD in type 2 diabetes mellitus have varied widely from 10% to 85% [6][7][8][9][10]. One joint analysis of available data on the prevalence of NDRD among patients with type 2 diabetes mellitus revealed that NDRD was evident on kidney biopsy in ∼22% of European and 26.7% of Asian patients [11].…”
Section: Introductionmentioning
confidence: 99%